Asociación entre las alteraciones visuales y el retraso del desarrollo motor en niños de 0 a 12 años: revisión narrativa de literatura. (2022)
Objective: To describe the association between visual disturbances and delayed fine and gross motor development in children aged 0 to 12 years reported in the scientific literature. Methodology: The information search was carried out in the databases: PUBMED, SciELO, Redalyc. English-language publications made between 2000 and 2021 were selected. These publications were characterized and evaluated with the CASPe critical reading method and finally the visual disturbances with their reported motor disturbances were grouped and classified. Results: Compared with control children, children with impaired binocular vision (strabismus and amblyopia) and visual impairment due to pathological causes; present alterations of fine and gross motor skills in different aspects. Conclusions: According to the literature review, there may be an association between binocularity disorders such as amblyopia and strabismus with the development of fine motor functions, while low vision and blindness can equally affect the development of fine and gross motor functions.